Pola Komunikasi Masyarakat Kajang Ammatoa dalam Menjaga Hutan - Rina M, Diana; Hamna, Dian Muhtadiah; Znow, Fitra Alim (Journal of Communication Sciences (JCoS), 2024)
This research aims to find out the communication patterns of the Kajang Ammatoa community in protecting the forest and what are the inhibiting factors in protecting the forest. This research method uses qualitative research and the type of research used is a case study. The informants in this study were 5 people. Data collection techniques in this study are observation, interviews, and documentation studies. Data analysis techniques used in this research are data reduction, data presentation, conclusion drawing. The results of this study indicate that the communication patterns of the Kajang Ammatoa community in protecting the forest refer to primary, secondary, linear, and circular communication patterns.